การศึกษาความเป็นไปได้ของแพลตฟอร์มการให้บริการการขึ้นรูปต้นแบบแม่พิมพ์ด้วยเครื่องพิมพ์สามมิติสำหรับอุตสาหกรรมเครื่องประดับ - ดนูพัฒน์ รัตนบันรินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research is a feasibility study of using a 3D printer service platform to create wax models in the jewelry business. Our goal is to investigate elements that influence innovation adoption of a 3D printer service online platform and online jewelry marketplace. Designers, Jewelry Traders, 3D Printer Service Providers, and Internet Users are four sample groups in this study. The research methodologies are qualitative research to investigate the elements that affect users and 3D Printer service providers, with a sample group of three 3D Printer service providers and three jewelry industry users. We create a user interface design of the 3D Printer service platform and jewelry marketplace platform in order to examine the elements that influence innovation adoption and build a methodology for quantitative research with 227 internet users. According to the findings of this survey, 62 percent of users from the overall sample group are interested in online jewelry marketplace prototype platform and 75 percent of 20 people who have experienced in 3D Printer services are interested in 3D Printer platform.